2019
DOI: 10.1016/j.jocn.2019.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical thrombectomy for recurrent large vessel occlusion

Abstract: Although mechanical thrombectomy (MT) has been shown in numerous trials to be a successful treatment option for patients with large vessel occlusion (LVO), there is limited information on the safety and effectiveness of the technique in cases of recurrent LVO. To this end, we performed a retrospective review of our prospectively maintained database to identify all patients that had undergone more than one MT procedure January 2008 and January 2018. The data collected on these patients included baseline demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Stroke cause was mainly cardioembolic (67%), which is in line with the findings from the previous case series on rEVT (66%, 43%, 87%). [6][7][8] In our series, most patients were on secondary prevention at the time of the recurrent LVO. However, in patients using anticoagulants, international normalized ratio often was not in the therapeutic range, which may have contributed to a recurrent event.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Stroke cause was mainly cardioembolic (67%), which is in line with the findings from the previous case series on rEVT (66%, 43%, 87%). [6][7][8] In our series, most patients were on secondary prevention at the time of the recurrent LVO. However, in patients using anticoagulants, international normalized ratio often was not in the therapeutic range, which may have contributed to a recurrent event.…”
Section: Discussionmentioning
confidence: 76%
“…Bhogal et al 8 report similar outcome for patients treated for contralateral LVO's. We agree with the authors that a larger sample size is needed before conclusions can be drawn.…”
Section: Stroke February 2020mentioning
confidence: 80%
“…To the best of our knowledge, there are five series of 15, 23, 25, 27 and 35 patients (Table 3) and several case reports regarding endovascular treatment of recurrent LVO. [5][6][7][8][9][10][11][12][13][14] In the available series to date, Bouslama et al 5 found that the incidence of recurrent LVO was 2% with the median time interval between the first and last procedure of recurrent LVO being 18 days. Similarly, Weber et al 11 found the incidence of recurrent LVO as 1.4%; however, the mean time interval between the first and second MT was 147 days.…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding the outcome of patients treated with repeated MT for recurrent LVO are also limited, and only a few series and several case reports have been published to date. [5][6][7][8][9][10][11][12][13][14] These reports vary in the interval of re-thrombectomy, from early recurrence (<1 day) up to over a year. 5,9,[11][12][13][14] In the present study, we report our experience with the endovascular treatment of patients with recurrent LVO, including three cases of target vessel re-occlusion.…”
Section: Introductionmentioning
confidence: 99%
“…Our patient with acute posterior circulation infarction and underlying ICAD underwent ET of the same occluded BA thrice within 24 h. Data on repeated ET for early recurrent stroke caused by the occlusion of the same affected vessel are scarce. To our knowledge, there are only a few case reports [3-5, 12] and two retrospective studies with repeated ET due to recurrent LVO [13, 14], but mostly in the anterior circulation. Our case report is the first on repeated ET within the BA.…”
Section: Discussionmentioning
confidence: 99%